2022
DOI: 10.3390/vaccines10060877
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Adverse Events Following Immunization (AEFI) after Third Dose Booster Vaccination with mRNA-Based Vaccine in Universitas Indonesia Hospital Health Personnel

Abstract: Facing the rising cases of with higher fatalities COVID-19, some countries decided to give the third dose of vaccine as a booster. As of 9 January 2022, 90.31% of health workers in Indonesia have received the third dose vaccine. This study aims to provide an evaluation of adverse events following immunization (AEFI) in a single center in Indonesia to form a basis for ensuring safety for booster administration nationally. A retrospective, cross-sectional study was conducted using an online survey. Demographic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…This study result is similar with the previous study by Pakki et al among health workers that 45.6% subjects were <35 years, which also indicated gender has no relationship with AEFI [12]. A study by Hidayat et al found that there was a significant relationship between the appearance of AEFI symptoms and a previous history of allergies [19]. Kadali et al also found a relationship between a history of COVID-19 infection and the AEFI in the mRNA-1273 vaccine [20].…”
Section: Aefis With Systemic Symptomssupporting
confidence: 90%
See 3 more Smart Citations
“…This study result is similar with the previous study by Pakki et al among health workers that 45.6% subjects were <35 years, which also indicated gender has no relationship with AEFI [12]. A study by Hidayat et al found that there was a significant relationship between the appearance of AEFI symptoms and a previous history of allergies [19]. Kadali et al also found a relationship between a history of COVID-19 infection and the AEFI in the mRNA-1273 vaccine [20].…”
Section: Aefis With Systemic Symptomssupporting
confidence: 90%
“…AEFI is influenced by age and gender, but people with a history of allergies, comorbid diseases, and those with a history of COVID-19 infection may also experience an AEFI reaction after being vaccinated. According to Hidayat et al age <25 years was found to have a significant effect on the AEFI [19]. This finding is in line with another study stated that the AEFI, was higher in the younger age group than at the elderly age group [13], [32].…”
Section: Aefis With Systemic Symptomssupporting
confidence: 81%
See 2 more Smart Citations
“…As such, researchers have emphasized the need to enhance the perception of vaccine safety to promote vaccine uptake ( 56 ). To accurately reflect the safety profile of the vaccine, researchers suggest implementing surveillance programs of adverse events ( 57 , 58 ) and systematic use of causality assessment ( 59 ). By providing scientific and practical evidence for limitations and possible side effects, these programs could bolster the perceived vaccine safety and increase public confidence in the vaccination program.…”
Section: Discussionmentioning
confidence: 99%